Diabetic Retinopathy in the Context of Patients with Diabetes - Simó-Servat, Olga; Hernández, Cristina; Simó, Rafael (Ophthalmic research, 2019)
Diabetic retinopathy (DR) is the most frequent complication of diabetes. The main risk factors are disease duration, a poor glycemic control, and the presence of hypertension. However, there is an important variation in risk which indicates that other factors, such as genetic heritability or glycemic variability, play an important role in accounting for the susceptibility to DR development. Another important concept is that DR is an independent predictor of both microvascular and macrovascular complications. Thus, the presence of DR should be taken into account when evaluating the cardiovascular risk of a diabetic subject. Moreover, the evaluation of retinal neurodegeneration could help to identify those diabetic subjects at risk of cognitive impairment, an emerging complication of the type 2 diabetic population. When evaluating a diabetic subject, the awareness of the presence of DR has also therapeutic implications. In this regard, a worsening of DR could occur after a rapid improvement of blood glucose. In summary, a critical review on the importance of the presence of DR in the general management of subjects with diabetes is provided.